The Effect of Spiritual Expressive Writing Therapy on Anxiety - Hasanah, Iswatun; Aisa, Anna (Jurnal Psikologi Islam dan Budaya, 2025)
The research aims to determine the effectiveness of expressive writing in reducing anxiety in research subjects. Pre-experimental Design research approach with One-Group Pre test-Post test Design. The scale used is the HARS anxiety scale (Hamilton Anxiety Rating Scale) with 5 categorizations of anxiety levels and 14 questions. A purposive sampling technique was used to determine the research subjects, namely 15 students who showed scores of 28-41 (severe category). Intervention stages Recognition or Initial Writing, Examination or Writing Practice, Feedback, and Application to Yourself. Research results and data analysis using the Wilcoxon signed test with the Asymp.sig value. (2-tailed) 0.001 < 0.05 then Ha is accepted, namely expressive writing is effective in reducing anxiety in research subjects.